Factors affecting outcome of treatment of chronic hepatitis C: result of an open label study from eastern India. (January 2016) - Ray, Gautam
Background: Standard treatment of hepatitis C involves the use of pegylated interferon (PEGIFN) and ribavirin but directly acting antiviral agents (DAA) with seemingly greater efficacy have now appeared on the market. Thus closer detail needs to be given to optimise the use of the former. Methods: Fifty-two chronic hepatitis C patients (Child class A) were administered PEGIFN and ribavirin in a prospective, open label study in standard dose and duration. Complete therapy was ensured for the best chance of achieving a sustained viral response (SVR) and delineating its controlling factors. Results: Seventy-five percent had genotype 3 virus. Compensated cirrhosis was present in 38.5%. Response overall and in cirrhotics were 65.4% and 30%, respectively, without difference between genotypes 1 and 3. Non-cirrhotics had higher response in all groups, especially genotype 1 (83.3%). The factors associated with positive response were age less than 50 years, absence of cirrhosis and presence of risk factors for transmission. Conclusion: Treatment outcome and factors affecting it are similar to studies from Europe and America.